Investigation of the features of the structural organization of inulin and analysis of the possibilities of its application - V. A. Byzov; V. V. Litvyak; N. D. Lukin; V. V. Shilov; Yu. F. Roslyakov; J. K. Irmatova (Новые технологии, 2024)
Investigation of inulin and the possibilities of its use is a relevant and important scientific and practical task. The goal is to study the features of the structural organization of inulin and analyze the possibilities of its use. The object and methods of the research. The object of the research was inulin obtained from Jerusalem artichoke roots. Photography (macro photography) was carried out using a SONY NEX-5N camera (Thailand). The microstructure was studied using an Olympus CX41RF light microscope (magnification 40, 100 and 400 times), ALTRA 20 Soft Imaging Sistem camera (Japan). IR absorption spectra were recorded on a Perkin Elmer Spectrum 1000 single-beam Fourier spectrometer in the spectral range of 400–4000 cm–1 with a spectral slit width of 4 cm–1; the recording time for one spectrum was about 2 min. The literature search on the problem was carried out in the databases of RSCI, Google Scholar, ResearchGate, PubMed using keywords and phrases: «inulin», «inulin structure», «inulin properties», «use of inulin», «fructo-oligosaccharides».The results and their discussion. Analysis of the IR spectrum has confirmed that inulin is a polysaccharide consisting of fructose residues. Studies of the morphology of inulin using light microscopy have shown that inulin is organized in the form of pseudocrystalline formations. In a medium of 96% ethyl alcohol, the central (in the form of a dark circle) and peripheral parts (in the form of a translucent circle that envelops the central dark circle), as well as small parts of inulin (in the form of dark dots) separating from the main pseudocrystalline formations, are clearly visible. There is a wide variety of foods fortified with inulin. It has been established that inulin concentrations used for food fortification vary widely depending on the type of food product, ranging from 0.75 to 50%. The prebiotic effect of inulin has been proved, but its interaction with various food matrices is a complex process, and it is not always technologically beneficial for the product. In addition to sensory, physicochemical and rheological characteristics, it is also necessary to measure characteristics such as prebiotic content of foods and determine prebiotic activity in vivo and in vitro, as well as evaluate potential adverse reactions in order to determine scientifically based doses of inulin for consumers.Conclusion. The obtained IR spectrum confirms the known chemical structure of inulin. Morphological studies of inulin using light microscopy indicate the creation of pseudocrystalline formations by inulin in a medium of glycerol and 96% ethyl alcohol. Inulin can be widely used in various foods as an important biologically active substance.